2015
DOI: 10.3389/fonc.2015.00068
|View full text |Cite
|
Sign up to set email alerts
|

The “Macro” World of microRNAs in Hepatocellular Carcinoma

Abstract: Hepatotropic viruses such as hepatitis B virus (HBV) and hepatitis C virus (HCV) are the major etiological agents associated with development of hepatocellular carcinoma (HCC). Progression of HCC is a multistep process that requires sequential or parallel deregulation of oncogenic and tumor suppressive pathways leading to chromosomal instability and neoplastic phenotype. In the recent years, microRNAs (miRNAs) have carved their own niche alongside oncogenes and tumor suppressors, owing to their innate ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 98 publications
(119 reference statements)
0
26
0
Order By: Relevance
“…Before they become metastatic and invasive, tumor cells undergo epithelial-mesenchymal transition (EMT), which is characterized by increased vimentin and loss of E-cadherin. 71,72 It was reported that the EMT-inducing transcription factor, Twist 1 increased the expression of Cul2 circRNA (circ-10720). 68 A positive correlation was found between circ-10720 and tumor malignancy and poor HCC progress.…”
Section: Circrnas In Hccmentioning
confidence: 99%
“…Before they become metastatic and invasive, tumor cells undergo epithelial-mesenchymal transition (EMT), which is characterized by increased vimentin and loss of E-cadherin. 71,72 It was reported that the EMT-inducing transcription factor, Twist 1 increased the expression of Cul2 circRNA (circ-10720). 68 A positive correlation was found between circ-10720 and tumor malignancy and poor HCC progress.…”
Section: Circrnas In Hccmentioning
confidence: 99%
“…miRNAs are small noncoding RNAs that regulate mammalian gene expression by binding with mRNAs. Moreover, a recent study reported that eight circulating miRNAs (miR-20a-5p, miR-25-3p, miR-30a-5p, miR-92a-3p, miR-132-3p, miR-185-5p, miR-320a, and miR-324-3p) are significantly overexpressed in HBV-positive HCC patients compared with HBV-positive cancer-free controls (Sidhu et al, 2015). Aberrant miRNAs has been measured in formalin-fixed paraffinembedded tissues of several tumor types, including HCC, lung cancer, melanoma, pancreatic cancer, papillary thyroid carcinoma, and renal tumors .…”
mentioning
confidence: 99%
“…They are non-coding microregulators of ~22 nucleotides in length, which are involved in the regulation of hepatocarcinogenesis (1). miRs may function as oncogenes or as tumor suppressors.…”
mentioning
confidence: 99%